Analysis of Local Economic Potential and Economic Competitiveness in Surabaya City - Yusuf Hariyoko; Anggraeny Puspaningtyas (Iapa Proceedings Conference, 2019)
Abstract Law Number 23 of 2014 concerning Regional Government clause 29 verse 5 explains that "The strategy for accelerating regional development as referred to in clause (4) covers the priority of development and management of natural resources in the sea, acceleration of economic development, socio-cultural development, humans development resource, development of customary law related to sea management, and community participation in development. Economic growth is one indicator of economic success in Indonesia, but in the course of economic growth there are several economic problems. The main economic problems according to Adisasmita (2005: 201) are (i) consumption; (ii) production; (iii) distribution; and (iv) growth. Economic growth of Indonesia depends on the production of goods and services in the real sectors produced. Surabaya is the second largest city after Jakarta in Indonesia, it is important to explore local economic potential and regional economic competitiveness to encourage the acceleration of the regional economy. The potential of local economic may not be competitive with all districts in the East Java Economic Province. Location Quotient and Shift Share analysis can be a basic calculation method for determining the acceleration of economic development in a region. Based on the Location Quotient analysis, it can be seen that the three main potentials of the local economy are the company's service sector (LQ = 3.056); and the sector of providing accommodation and food drink (LQ = 2,818); financial and insurance sector (LQ = 1,937). While the three main sectors that are competitive are large and retail trade (SS = 11,172.2); car and motorcycle repair sector (SS = 8,113,6); and the sector of providing accommodation and food drink and processing industries (SS = 7,616,7). It can be concluded that the leading sectors and competitive sectors can be used as the basis for accelerating the economic development of Surabaya City.